SISTEM INFORMASI PELAYANAN MASYARAKAT DI KELURAHAN PANARUNG, KECAMATAN PAHANDUT PALANGKARAYA BERBASIS WEB - Ade Chintia Desy; Enny Dwi Oktaviyani; Felicia Sylviana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2020)
Panarung village office, pahandut sub-district is one of the sub-districts located in the city of palangkaraya. In carrying out these tasks and functions, the Panarung village office does not yet have an information system that can support public service activities. All service processes are carried out manually. This study aims to create web based information system that can be used by outward employees in Panarung Village to carry out service activities to the people in the Panarung Village area using waterfall software development methods, PHP programming languages ??and MySQL databases. Testing using blackbox testing. Based on the test results, it can be concluded that this information system can be used for service activities to the community in the Panarung village